(untitled) (Journal of the College of Education for Women, 2019)
The current research aims to know the effect of teaching using multiple intelligences theory on academic achievement for students of primary school. The sample search of pupils . The research sample was divided into two groups where the first group represented the experimental group which studied the use of multiple intelligences and the second group represented the control group which studied the use of the traditional way . The search tool consisted of achievement test. Showed search results, there are statistically significant differences(0.05) between the average scores of students who have studied according to multiple intelligences between the average scores of students who have studied in accordance with the tradition way in the post-test.